Noncommutative algebras, context-free grammars and algebraic Hilbert series. (November 2020) - La Scala, Roberto; Piontkovski, Dmitri; Tiwari, Sharwan K.
Abstract: In this paper we introduce a class of noncommutative (finitely generated) monomial algebras whose Hilbert series are algebraic functions. We use the concept of graded homology and the theory of unambiguous context-free grammars for this purpose. We also provide examples of finitely presented graded algebras whose corresponding leading monomial algebras belong to the proposed class and hence possess algebraic Hilbert series.